2004
DOI: 10.1038/sj.emboj.7600247
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of ribosomal protein L11 in mediating growth inhibition-induced p53 activation

Abstract: The ribosomal protein L11 binds to and suppresses the E3 ligase function of HDM2, thus activating p53. Despite being abundant as a component of the 60S large ribosomal subunit, L11 does not induce p53 under normal growth conditions. In search of mechanisms controlling L11-HDM2 interaction, we found that the induction of p53 under growth inhibitory conditions, such as low dose of actinomycin D or serum depletion, can be significantly attenuated by knocking down L11, indicating the importance of L11 in mediating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
261
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(275 citation statements)
references
References 39 publications
10
261
0
Order By: Relevance
“…Analysis of polysomal profiles of both starved and rapamycintreated cells (Figures 3c and g) indicated that the global rRNA transcription modulates p53 G Donati et al level of protein synthesis also was reduced in these conditions, in comparison with control cells. These data were consistent with the absence of p53 stabilisation after serum deprivation observed in TGR-1 cells (Ho¨lzel et al, 2005), but not with the reported activation of p53 in WI-38 cells after serum starvation (Bhat et al, 2004), thus suggesting that serum starvation may induce a cell-specific p53 activation.…”
Section: Polr1a Silencing Stabilises P53 Without Disrupting the Nuclesupporting
confidence: 87%
See 1 more Smart Citation
“…Analysis of polysomal profiles of both starved and rapamycintreated cells (Figures 3c and g) indicated that the global rRNA transcription modulates p53 G Donati et al level of protein synthesis also was reduced in these conditions, in comparison with control cells. These data were consistent with the absence of p53 stabilisation after serum deprivation observed in TGR-1 cells (Ho¨lzel et al, 2005), but not with the reported activation of p53 in WI-38 cells after serum starvation (Bhat et al, 2004), thus suggesting that serum starvation may induce a cell-specific p53 activation.…”
Section: Polr1a Silencing Stabilises P53 Without Disrupting the Nuclesupporting
confidence: 87%
“…In fact, the large subunit ribosome proteins rpL5, rpL11 and rpL23 were all reported to bind MDM2, thus inducing p53 stabilisation by inhibiting its E3 ubiquitin ligase function (Lohrum et al, 2003;Zhang et al, 2003;Bhat et al, 2004;Jin et al, 2004). The impairment of the nucleolar function has been proposed as a common denominator of many signalling pathways leading both to the suppression of MDM2 function and to p53 stabilisation and activation (Rubbi and Milner, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Given the presumed importance of specific RPs to inhibit Mdm2, it would seem logical that depletion of these Mdm2-binding partners would mitigate a p53-dependent response. This seems to be the case for Rpl11 (Bhat et al, 2004), Rpl5 , Rps7 (Zhu et al, 2009) and Rps3 (Yadavilli et al, 2009) where, in the absence of stress, small interfering RNA knockdown had no effect on p53 stability. However, this was not the case for Rpl23, which was not only found to bind to and regulate the Mdm2-p53 interaction, but was also found to cause p53-dependent cell cycle arrest when depleted in cell culture models .…”
Section: Rp Imbalances Activate P53mentioning
confidence: 90%
“…Nearly a decade later, in screens seeking out novel Mdm2 modulating proteins, the large subunit RPs RPL5, RPL11 and RPL23 were all reported to bind to Mdm2, block the E3 ubiquitin ligase function of Mdm2, and promote p53 accumulation (Lohrum et al, 2003;Zhang et al, 2003;Bhat et al, 2004;Jin et al, 2004). Following these initial reports, additional evidence subsequently was produced to support the roles of RPS7 (Chen et al, 2007;Zhu et al, 2009), RPL26 (Ofir-Rosenfeld et al, 2008 and RPS3 (Yadavilli et al, 2009) as Mdm2-binding partners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation